6. Kajian Jenis dan Potensi Ikan di Hutan Lindung Angke Kapuk, Penjaringan, Jakarta Utara - Gema Wahyudewantoro (Fakultas Perikanan Universitas Pekalongan, 2016)
The survey was conducted at Angke-Kapuk Protected Forest, Penjaringan-North Jakarta. The aim of research was to know of fish based diversity and potency. Fish caught with gillnet (mesh size ¾, 1,5 and 2 inch) and fishnet (mesh size 1,5 and 2,0 cm). The result were recorded 19 species belongs to 18 genera and 14 family. Guppy was dominant spesies, while the potential economic are sepat, bulan-bulan and mullet. Key words: protected forest, potency, fish, angke kapuk